Diseño de un plan estratégico de mercadeo para la empresa U2 Printer S.A.S. (2019)
In the present study of a model for the analysis of the U2 Printer S.A.S. company is proposed, in order to characterize it and make a typology of it. The contrast of the model is made through the development of a strategic plan, which through various tools will show the impact of the company in the advertising sector, and thanks to the strengths, weaknesses, opportunities and threats, we will develop specific strategies that will impact the development of the organization.